Water Quality of Ranowangko River That Crosses Tomohon City and Minahasa Regency, North Sulawesi Province - Tumanduk, Yahya Y.R.; Naharia, Orbanus; Sumampouw, Herry M.; Ogi, Nova L.I.M.; Gedoan, Sukmarayu P.; Mokosuli, Yermia S. (Jurnal Biologi Tropis, 2024)
The Ranowangko River passes through Tomohon City and Minahasa Regency, ending in the Sulawesi Sea. Tombariri District, is the Bunaken National Park area. Ranowangko River Water Monitoring in 2022 by the Regional Environmental Service of North Sulawesi Province shows that Fecal Coli and Total Coli parameters in the Ranowangko River at Station 1 do not meet the requirements according to Government Regulation Number 22 of 2021 concerning Class 2 National Water Quality Standards (BMA). Research to assess water quality from biological, physical and chemical aspects as well as determine water quality status. Monitoring was carried out 4 times in 2 consecutive years at 3 observation stations. Quantitative data and qualitative data include water quality analysis through determination of 14 parameters compared according to BMA Class 2. The water quality data was analyzed using the Storet Method to determine water quality status in accordance with Minister of Environment Decree Number 115 of 2003. The results showed Fecal Coli and Total Coli (Biological Aspects), TSS (Physical Aspects), Total Phosphate (Chemical Aspects) exceeded the BMA. Score calculation results using the Storet method at Station 1: -68, Station 2: -72 and Station 3: -76. Based on the value system According to Minister of Environment Decree 115 of 2003, the score above shows that the Water Quality Status of the Ranowangko River is heavily polluted. Recommendations to the regional governments of Tomohon City and Minahasa Regency to carry out further monitoring of the water quality of the Ranowangko River.